Does light pollution affect zebrafish embryos response to mycophenolic acid? - Costa, Maria Santos de Sousa e (2023)
In recent years, the process of urbanization has led to a significant escalation in light pollution within natural aquatic ecosystems. This light pollution, resulting from the increased presence of artificial light at night (ALAN), disrupts natural light levels. ALAN disturbs circadian rhythms by inhibiting the nighttime secretion of melatonin. Urban freshwater environments, in addition to contending with light pollution, are also subject to chemical contamination due to improper disposal, pharmaceutical residues in organic fertilizers, and wastewater from urban areas and healthcare facilities, pharmaceuticals such as antineoplastic drugs, which are continuously released into the environment and accumulate in various ecosystems. The aim of this work was to assess whether ALAN alters the response of Danio rerio embryos to the antineoplastic drug mycophenolic acid (MPA). To assess embryos response to MPA the organisms were exposed to a set of concentrations ranging from 16 to 288 μg/L for 120 hours. Embryos’ mortality, hatching, and malformations rates were observed every 24 hours for the 120 hours of exposure, and heart rate was assessed at 48 hours. Moreover, at the end of the exposure, a behaviour test was performed on larvae and the body length, interocular distance, and swimming bladder size were measured, and a set of biochemical biomarkers related with oxidative stress, neurotoxicity and energy metabolism were analysed. To assess ALAN effects and its interaction with MPA, embryos were exposed to three different light intensities (0, 1 and 10 lux) and four different MPA concentrations (0, 36, 90 and 225 μg/L). The same endpoints as in the MPA experiments were analysed. The results indicate that MPA decreases survival of embryos and impairs the normal development of zebrafish embryos, by decreasing hatching rate and inducing malformations. At behavioural level, the exposure to this cytostatic drug also affected the swimming behaviour of zebrafish larva. Furthermore, MPA affected the antioxidant system of zebrafish embryos and altered their energy metabolism. No effects of ALAN were observed for D. rerio life history traits, but it led to an earlier onset of malformations induced by MPA, reduced the behavioural response to MPA and modified MPA responses at a biochemical level, namely catalase activity, protein, and carbohydrate contents. In conclusion, ALAN has the potential to modify the response of D. rerio embryos to MPA, thus underscoring the relevance of including it in ecological risk assessments of antineoplastic drugs. Nevertheless, the precise underlying mechanisms remain unidentified. The findings of this work emphasize the critical need to investigate the combined impacts of chemical contamination and light pollution, both prevalent and concomitant stressors in urban freshwater ecosystems.